Segmented Markets, Cooperative Behaviours: Innovation in the Production of Brazilian Coffee - Lúcia Urban; Teresa Noronha Vaz (European Regional Science Association (ERSA), 2010)
The present article aims to discuss some the organizational and institutional aspects that have became the basis for the development of coffee as a non-commodity product in Brazil. It is expected that due to new patterns of coffee consumption, a new strategy permits the competitive reinsertion of Brazilian coffee into the international markets. This paper discusses some of the major aspects of contemporary industrial organization requirements imposing process innovation along the supply chain of many agro-food products around the world. It is argued that they are connected to a new industrial order, related to differentiation and/or segmentation processes. The suggested methods, interviews to the driving stakeholders and accompanied observation of their networking systems, are applied in the different stages of the supply chain in order to demonstrate that the production conditions are imposing strategic interrelationships between the roasting and the grinding industry and among the several intervenient agents. It is further observed that most of such processes take place within a new context of competition where innovation, segmentation and product differentiation are more important factors for the international market than cost and price reductions, thus thereby demanding a serious redefinition the companies' strategies. The results detect the application of the concept of flexible specialization as a fundamental input. They corroborate some of the analytical elements which are essential to explain export revitalization actions acquired from specific attributes such as, for example, highly qualified managers, able to adapt to continuous innovation. It was also observed that, for the whole productive segment, the qualified management reflects a strategy that is inserted into a wider policy issue. In this successful case, companies and government have closely interacted in order to provide the ideal conditions to overcome the global competition by means of benchmarking and differentiated consumption standards. Finally, another major conclusion is that there exists an historical capability of public and private interests to interact. Such has been decisive to ease difficulties arousing from market fluctuations and facilitate the required technical and institutional innovations.
Keywords: 330; Organizational Innovation; Segmentation; Cooperation; Brazilian Coffee